Personalized medicine: A step forward in dental treatment - Surbhi; Anand Kumar; Archna Nagpal; Puneeta Vohra (Wolters Kluwer Medknow Publications, 2015)
The study of variations of DNA and RNA characteristics as related to drug response is known as pharmacogenomics. The application of pharmacogenomics to the clinical management of an individual is referred to as "personalized medicine." Personalized medicine aims to individualize care based on a person's unique genetic profile by using advanced molecular tools like DNA profiling, gene mapping, receptor gene amplification test, fluorescence in situ hybridization (FISH), microarray test, Hercep Test, AmpliChip CYP450 Test, etc. This is relatively a new field that combines genomics (the study of genes and their functions) and pharmacology (the science of drugs) to develop effective, safe medications and doses that will be tailored to a person's genetic makeup. Now personalized medicine has a wide range of applications such as management of cancer, cardiovascular disorders, depression, bipolar disorders, attention deficit disorders, HIV, tuberculosis, asthma, diabetes, and also in the management of pain. This is the first article focusing on its mechanism, overview of the developments, benefits, challenges, and its applications, particularly in dentistry.